Avoiding armageddon : america, india, and pakistan to the brink and back - Riedel, Bruce O. ([S.l.] : HarperCollins Publishers India, 2013)
India and Pakistan will be among the most important countries in the twenty-first century. Born from the British Raj, they share a common heritage, but they are different in many important ways. India is already the world's largest democracy and will soon become the planet's most populous nation. Pakistan, soon to be the fifth largest in population, has a troubled history of military coups, dictators, and harboring terrorists, including Osama bin Laden. In Avoiding Armageddon , Bruce Riedel clearly explains the challenge and the importance of managing America's affairs with these two emerging powers and their toxic relationship. Both longtime rivals are nuclear powers, with tested weapons. They have fought four wars with each other and have gone to the brink several other times. Meanwhile, U.S. presidents since Franklin Roosevelt have been increasingly involved in the region's affairs. In the past two decades alone, the White House has intervened to keep the subcontinent from going to nuclear war on several occasions, and of course America is now also fighting its longest war ever in Afghanistan. South Asia is critical to American national security, and the volatile relationship between India and Pakistan is the crucial factor determining whether the region can ever be safe and stable. Based on extensive research and Riedel's role in advising four U.S. presidents on the region, Avoiding Armageddon reviews the history of American diplomacy in South Asia, the crises that have flared in recent years, and the prospects for future crisis. A product of the Brookings India Project, the book provides an in-depth look at the Mumbai terrorist attack in 2008, the worst terrorist outrage since 9/11. Riedel concludes with authoritative analysis on what the future is likely to hold for America and the South Asia.
Keywords: India; International relations; Nuclear arms control; Pakistan; South Asia; Terrorism--Prevention; United States